Promoting Third Sector Leadership: Letting a Thousand Flowers Bloom - Addarii, Filippo (Institutional Knowledge at Singapore Management University, 2009)
How do we foster leadership and social innovation in the third sector? Filippo Addarii and Ben Rattenbury share a European method through the peer-led Euclid Network.